Sex differences in Drosophila behavior: Qualitative and Quantitative Dimorphism - Asahina, Kenta (Curr Opin Physiol, 2018)
The importance of sex as a biological variable is being recognized by more and more researchers, including those using Drosophila melanogaster as a model organism. Differences between the two sexes are not confined to well-known reproductive behaviors, but include other behaviors and physiological characteristics that are considered “common” to both sexes. It is possible to categorize sexual dimorphisms into “qualitative” and “quantitative” differences, and this review focuses on recent advances in elucidating genetic and neurophysiological basis of both qualitative and quantitative sex differences in Drosophila behavior. While sex-specific behaviors are often mediated by sexually dimorphic neural circuits, quantitative sexual dimorphism is caused by sex-specific modulation of a common neuronal substrate.